Essential nutrients and oxidative stress of durum wheat under water stress. - Ghozlène, Issaad; Mohammed-Réda, Djebar; Houria, Berrebbah; Ali, Charga (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
Oxidative stress in plants is the subject of numerous reviews of the literature (Apel and Hirt, 2004; Noctor and Foyer, 2005a; Pitzschke et al, 2006;. Wormuth et al, 2007;. Sbartai et al, 2012.) And of several books (Inze and Montagu, 2001; Smirnoff et al, 2005.). This work focuses on studying the effects of water stress on the roots of a plant model: durum wheat (Triticum durum) variety GTA. After the germination, the plants were subjected to water stress during (03, 05, 07 and 09 days). Our results demonstrate abiochemical and metabolic disturbances of the seed subjected to water deficit. The lack of water has caused significant changes in the GTA durum variety.